Synthesis and anion recognition studies of new ureylbenzamide-based receptors. Issue 1 (2nd January 2018) - Moreno-Valle, Bibiana; Aguilar-Martínez, Milagros; Ochoa-Terán, Adrián; Martínez-Quiroz, Marisela; Miranda-Soto, Valentín; García-Elías, José; Ochoa-Lara, Karen; Labastida-Galván, Victoria; Ordoñez, Mario
Abstract: A new group of ureylbenzamide-based receptors (1 –4 ) has been synthesized; its binding affinity and capacity to form supramolecular complexes in solution with different anions have been investigated. For designing these receptors, it was considered a combination of the positions of the urea and amide groups ( ortho and meta ), and the chromophore groups naphthyl and nitrophenyl, yielding four receptors. The position and chromophore structure affected the acidity of the urea and amide hydrogens in the order4 >3 >2 >1 . All the spectroscopic studies showed a significant change of1 and2 compared with3 and4 in the presence of different TBAX salts in acetonitrile. The 1 H-NMR spectra show a preferential interaction of the anions with the urea group in receptors1 and2 due to the less steric hindrance, while there is a cooperative interaction of amide group in receptors3 and4 due to the closeness of both groups. Abstract :